2015
DOI: 10.4103/0366-6999.162507
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Glucose Metabolism in Olfactory Bulb is an Earlier Alzheimer's Disease-related Biomarker in 5XFAD Mice

Abstract: Background:Early diagnosis assumes a vital role in an effective treatment of Alzheimer's disease (AD). Most of the current studies can only make an AD diagnosis after the manifestation of typical clinical symptoms. The present study aimed to investigate typical and other biomarkers of AD to find a possible early biomarker.Methods:A total of 14 5XFAD mice (at 3 and 6 months old), with 14 age-matched wild-type (WT) mice as control, were enrolled in this case-control study. Morris water maze test was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 36 publications
6
40
0
Order By: Relevance
“…Macdonald et al ( 12 ) described a significant decrease of 18 F-FDG uptake in 13-month-old 5XFAD mice, while younger animals did not show differences in the whole brain SUV compared to WT. Another study by Xiao et al ( 40 ) reported lower 18 F-FDG uptake in the cerebral cortex, hippocampus and olfactory bulb of 6-month-old 5XFAD mice. Hypometabolism within the olfactory bulb was detected as early as 3 months of age ( 40 ).…”
Section: Discussionmentioning
confidence: 90%
“…Macdonald et al ( 12 ) described a significant decrease of 18 F-FDG uptake in 13-month-old 5XFAD mice, while younger animals did not show differences in the whole brain SUV compared to WT. Another study by Xiao et al ( 40 ) reported lower 18 F-FDG uptake in the cerebral cortex, hippocampus and olfactory bulb of 6-month-old 5XFAD mice. Hypometabolism within the olfactory bulb was detected as early as 3 months of age ( 40 ).…”
Section: Discussionmentioning
confidence: 90%
“…The widely used 5XFAD mouse line express a total of five human APP and PSEN-1 transgenes, which results in rapid onset of amyloid plaques throughout the cortex and hippocampus as early as two months of age (Oakley et al, 2006) and could, therefore, be used to assess site-specific amyloid pathology associated with alcohol exposure. The 5XFAD mouse line also shows a deficit in spatial memory (Xiao et al, 2015) suggesting that cognitive decline associated with amyloid pathology can be modeled in APP / PSEN-1 transgenic mouse lines.…”
Section: Translational Approach: Selection Of the Triple-transgenic Mmentioning
confidence: 99%
“…The Papez circuit enables the connection between the cingulate gyrus and hippocampus, and it plays an important role in memory function [ 43 ]. Recently, the hypometabolism of the olfactory bulb has served as a potential marker of the diagnosis of AD and is related to memory deficits [ 44 , 45 ]. Although some studies suggested that A ÎČ deposits in this area may promote AD pathology [ 46 , 47 ], another study has found that the deposition of the TAR DNA-binding protein of 43 kDa (TDP-43) in the olfactory bulb was associated with AD and associated symptoms including episodic memory loss and hippocampal atrophy [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%